2020
DOI: 10.1111/epi.16454
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of focal to bilateral tonic‐clonic seizures during long‐term video‐EEG monitoring

Abstract: Objective To determine predictors of focal to bilateral tonic‐clonic seizures (FBTCS) during video–electroencephalography (EEG) monitoring (VEM). Methods All adult patients undergoing presurgical VEM from 2014 to 2015 in the department of epileptology were eligible (N = 229). Those with refractory focal epilepsy and epileptic seizures recorded during VEM were analyzed (N = 188, Group 1). To assess the effects of antiepileptic drug (AED) taper, the total AED load was calculated as the sum of the ratios of presc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Specifically, it is well‐known that AED changes and withdrawal can change the severity and evolutions of seizures. For example, bilateral tonic–clonic seizures are more prevalent when AED levels are reduced (Pensel et al, 2020). AEDs have further been shown to impact inter‐ and peri‐ictal brain activity (Badawy, Macdonell, Jackson, & Berkovic, 2009; Meisel et al, 2015), making it an important feature to consider.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, it is well‐known that AED changes and withdrawal can change the severity and evolutions of seizures. For example, bilateral tonic–clonic seizures are more prevalent when AED levels are reduced (Pensel et al, 2020). AEDs have further been shown to impact inter‐ and peri‐ictal brain activity (Badawy, Macdonell, Jackson, & Berkovic, 2009; Meisel et al, 2015), making it an important feature to consider.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, it is wellknown that AED changes and withdrawal can change the severity and evolutions of seizures. For example, bilateral tonic-clonic seizures are more prevalent when AED levels are reduced (Pensel et al, 2020).…”
Section: Residuementioning
confidence: 99%
See 1 more Smart Citation
“…It is also well-known that AED changes and withdrawal can change the severity and dynamics of seizures. For example, bilateral tonic-clonic seizures are more prevalent when AED levels are reduced [37]. We were unable to include this information in the current study, but future studies may wish to investigate AED levels as additional potential explanatory variables for seizure dissimilarity.…”
Section: Discussionmentioning
confidence: 95%
“…In case of ASM tapering, a distinction can be made between taper dose and taper rate. Two studies have shown in multivariate analyses that taper dose affected the risk of an adverse event more so than taper rate (8,9).…”
Section: Factors That Determine the Risk Of Adverse Eventsmentioning
confidence: 99%